A interferência do vinculo entre os profissionais das Equipes de Saúde da Família da prefeitura de Belo Horizonte com os usuários e serviço do SUS seu impacto na Promoção de Saúde e na prevenção da violência - Sandra Cristina Paulucci Cavalcanti de Andrade (2020)
It’s a big Challenge for the Primary health care (APS) to qualify yours practices, with an objective of create a link between the authors, considering your relevance and the emergency of the problematic health care to achieve and make sure the integrity of care. The link between professionals from the family health teams (eSF), users of the Unified Health System (SUS) and PHC services is essential to keep the actions of the Family Health Program (PSF) whose impact is directly linked to the Promotion of Health and Violence Prevention. Establish a Link is a basic principle of Health Policies in Brazil, and your effectiveness may interfere in health, as it qualifies assistance and reduces tension between the subjects involved.The objective of this study is to evaluate the correlation of factors that help or not the formation of links between the professionals of the eSF, that acts in the APS of the Municipal Health Secretariat (SMSA) of the Municipality of Belo Horizonte (PBH), with your registered population and basic health unit (UBS). It is a study of quantitative design. A research was made, including all professionals inserted in the PHC present in the unit at the time of the survey and that signed the Informed Consent Form (ICF). A probabilistic sample of 1402 workers linked to the 45 UBS drawn, existing in the nine Regionals of the PBH, in 2017, answered a semi-structured questionnaire. The database built, based on the workers' responses, was analysed using the SPSS statistical package.The analysis of the studied sample revealed as interference in the formation of links: demographic social factors, worker profile, and characteristics of PHC services, job satisfaction and the influence of situations of violence experienced. The study showed that the chance of having a high link increased more than 50% depending on the gender, age, and level of graduation of the professionals. And yet, it demonstrated that a low link formation is related to those professionals who practiced some type of aggression to the user, or even were victims of violence. The results also pointed out that the chance of having a high linkincreases more than 80% if the professional is satisfied with the job. For that reason, its necessary to reflect and discuss the importance of identifying gaps and weaknesses in PHC, which in some way may influence the formation of links between those involved. The knowledge of the factors and elements present in the daily routine of assistance can bring strategies that reorganize the management and valorisation processes of the workers inserted in the PHC. Establishing a link requires a lot of changes in the organization of services and management, enphataizing professional training that values protagonist and autonomy, this is mainly provided by humanized relationships, with are essential for the continuity of the actions of the PSF. This work intends to stimulate new inquiries to subsidize public policies aimed at valuing interpersonal relationships in order to strengthen the link in PHC, providing integrality health care.